The Role of AI and Virtual Learning Environments in Enhancing STEM Education - Hasegawa, Tatsuhiro; Yamada, Haruto; Nishimura, Hanako; Kobayashi, Miyuki (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
The rapid development of educational technology, particularly Artificial Intelligence (AI) and Virtual Learning Environments (VLEs), has transformed STEM education globally. Japan, known for its technological advancements, is leveraging these innovations to enhance STEM education and prepare students for a technology-driven future. However, challenges such as teacher readiness, infrastructure limitations, and cultural barriers hinder their widespread adoption. This study aims to evaluate the effectiveness of AI and VLEs in improving student engagement and comprehension in Japan’s STEM education system, while identifying the challenges and opportunities for their integration. A mixed-methods approach, involving in-depth interviews, surveys, and case studies, was employed with 150 respondents: students, teachers, and educational technology developers. The findings indicate that AI and VLEs have a positive impact on student engagement, comprehension, and accessibility to complex STEM concepts. However, barriers such as high costs, insufficient teacher training, and infrastructure issues limit their effectiveness. Gender disparities in technology use and engagement were also noted, with female students reporting higher stress and lower engagement levels. Future research should focus on addressing the identified barriers, particularly through improved teacher training, infrastructure investments, and the development of more inclusive, adaptable learning platforms. Further studies could also explore the long-term impact of AI and VLEs on student outcomes across different educational levels and regions in Japan.